β-Lactoglobulin affects the oxidative status and viability of equine endometrial progenitor cells via lncRNA-mRNA-miRNA regulatory associations - Data, Krzysztof; Marcinkowska, Klaudia; Buś, Klaudia; Valihrach, Lukas; Pawlak, Edyta; Śmieszek, Agnieszka (Journal of cellular and molecular medicine, 2023)
The β-lactoglobulin (β-LG) was previously characterized as a mild antioxidant modulating cell viability. However, its biological action regarding endometrial stromal cell cytophysiology and function has never been considered. In this study, we investigated the influence of β-LG on the cellular status of equine endometrial progenitor cells under oxidative stress. The study showed that β-LG decreased the intracellular accumulation of reactive oxygen species, simultaneously ameliorating cell viability and exerting an anti-apoptotic effect. However, at the transcriptional level, the reduced mRNA expression of pro-apoptotic factors (i.e. BAX and BAD) was accompanied by decreased expression of mRNA for anti-apoptotic BCL-2 and genes coding antioxidant enzymes (CAT, SOD-1, GPx). Still, we have also noted the positive effect of β-LG on the expression profile of transcripts involved in endometrial viability and receptivity, including ITGB1, ENPP3, TUNAR and miR-19b-3p. Finally, the expression of master factors of endometrial decidualization, namely prolactin and IGFBP1, was increased in response to β-LG, while non-coding RNAs (ncRNAs), that is lncRNA MALAT1 and miR-200b-3p, were upregulated. Our findings indicate a novel potential role of β-LG as a molecule regulating endometrial tissue functionality, promoting viability and normalizing the oxidative status of endometrial progenitor cells. The possible mechanism of β-LG action includes the activation of ncRNAs essential for tissue regeneration, such as lncRNA MALAT-1/TUNAR and miR-19b-3p/miR-200b-3p.
Keywords: RNA, Messenger; antioxidancia; MicroRNAs; endometrium; mikro RNA; RNA dlouhá nekódující; RNA, Long Noncoding; laktoglobuliny; Stem Cells; Animals; β-lactoglobulin; Antioxidants; non-coding RNA; zvířata; Lactoglobulins; koně; progenitor cells; messenger RNA; kmenové buňky; Horses